DINAMIKA PEMBAHARUAN HUKUM KELUARGA ISLAM DI INDONESIA DAN KONFLIK KELUARGA HUKUM ADAT DIHUBUNGKAN DENGAN UU NO. 1 TAHUN 1974 JO UU NO. 16 TAHUN 2019 TENTANG PERKAWINAN - Saprudin, Nanang; Sayehu, Sayehu; Musthafa, Usman (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Marriage according to Customary Law is not only a very important event for those who are still alive, but marriage is also a very meaningful event and one that receives full attention and is attended by the spirits of the ancestors of both parties. Customary law does not regulate absolutely the age limit for a person's marriage, that is, there are no provisions regarding the minimum and maximum age limits for entering into marriage. One of these things is that the Outer Baduy community is allowed to marry at a young age. Thus, this research will examine the meaning of marriage, marriage in the outer Baduy community and legal sanctions for foreign Baduy customary marriages towards the marriage of underage children. The discussion method in this research is qualitative with the type of research namely the Normative legal approach (normative juridical) and Empirical Law (empirical juridical) or known as normative-empirical research. Meanwhile, the definition of an empirical juridical approach is carried out by looking at the realities that exist in practice in the field. The results and conclusions of this research are the foreign Baduy marriage process, if the legal conditions for the marriage are not met, then according to law number 1 of 1974 in conjunction with law number 16 of 2019 concerning marriage, it is explained that a marriage can only be said to be a valid marriage if it fulfills the following requirements. marriage requirements and carried out according to the laws of each religion and recorded according to statutory regulations. Then there are legal sanctions if there is a violation of underage marriage as regulated in Law no. 1 of 1974 in conjunction with Law no. 16 of 2019 concerning marriage, namely if there is an element of coercion in marrying a minor for any reason, criminal penalties can be imposed. Islamic law does not prohibit someone from entering into a marriage on condition that they have reached maturity and are able to provide a living, both physical and spiritual. The Baduy traditional community all obeys the rules made by Pu'un. In customary law there are also sanctions if there is a violation. The lightness or severity of the sanctions depends on the type of error or violation